Structures of solutions to the problems for multilayer media and their applications to the calculation of fuel–element thermal fields - Khazhmuradov, M.A. (Вопросы атомной науки и техники, 2001)
The technique of constructing approximate solutions to heat conduction problems of media is presented. The calculation is based on the structures of solutions constructed with the help of the left, normalized-to-the-first-order equations of region boundaries and their characteristic parts. The structures of solutions contain uncertain components, and whatever their choice may be, the boundary conditions and the conditions of medium conjugation are fulfilled exactly. The arbitrary choice of uncertain components is used to satisfy the basic differential equation.